Correction: An intravascular bioartificial pancreas device (iBAP) with silicon nanopore membranes (SNM) for islet encapsulation under convective mass transport. Issue 13 (9th June 2017) - Song, Shang; Blaha, Charles; Moses, Willieford; Park, Jaehyun; Wright, Nathan; Groszek, Joey; Fissell, William; Vartanian, Shant; Posselt, Andrew M.; Roy, Shuvo
Abstract : Correction for 'An intravascular bioartificial pancreas device (iBAP) with silicon nanopore membranes (SNM) for islet encapsulation under convective mass transport' by Shang Song et al., Lab Chip, 2017, 17, 1778–1792.